Water Sustainability Concept of Hindu Javanese Community Settlements Toward Global Climate Change Resilience in the Indonesia Mountainous Area - Fauzan Ali Ikhsan, Bambang Setioko and Atiek Suprapti (Nature Environment and Pollution Technology, 2022)
Traditional settlements in the mountains are most vulnerable to climate change impacts. The threat of water sustainability to support the life of a traditional residential area is one of the climate change challenges that must be faced. This research aims to explore the local wisdom of the Hindu Javanese community in regulating the landscape of its settlements to maintain water sustainability now. This research methodology used a qualitative approach. This study took place in a traditional settlement of the Hindu Javanese community in the Cetho Temple area. The Cetho Temple area is one of the traces of the remnants of the Majapahit kingdom civilization on Mount Lawu, which was built in the 15th century. Data collection techniques are conducted by direct observation and interviews of several purposively selected informants in the study area. Data analysis is done by analyzing data into physical data and socio-cultural data spatial analysis. The two groups of data were analyzed to obtain a complete picture of the strategy of the Javanese Hindu community to regulate water sustainability in residential areas. The research result shows that The Hindu Javanese community built its settlements concerning local topographic and hydrological conditions in maintaining water sustainability. The Mountain – Springs – Settlement - Farm field relationship forms an environmental ecosystem that is always balanced. In addition to maintaining physical water continuity, the Javanese Hindu community has a spiritual tradition to maintain the spirit of its people to maintain water continuity. The Hindu Javanese community in the Cetho Temple area can align settlements and nature through this local wisdom. This research in the future is expected to be useful as a reference for water management in traditional settlements in the mountains and planning for structuring settlement areas in the mountains.